2021
DOI: 10.1016/j.sjbs.2021.05.068
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of DNA damage in relation to heavy metal induced oxidative stress in females with recurrent pregnancy loss (RPL)

Abstract: Pregnancy termination consecutively for three or more times during the first trimester is termed as Recurrent pregnancy loss (RPL). In addition to the abnormal karyotype, heavy metal induced oxidative damage may contribute as prominent etiological factor in pregnancy termination. Oxidative stress is considered crucial in etiology underlying RPL with altered antioxidant status and subsequent DNA damage. The current case controlled study investigated Total antioxidant capacity (TAC), DNA damage (8OHdG) and heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 32 publications
0
18
1
Order By: Relevance
“…Among them, DNA methylation-induced gene expression disorders and immunological imbalances affect all phases of embryonic development, which may be linked to RPL pathobiology (29). In addition, clinical studies have found that DNA damage induced by heavy metals may be related to the occurrence and development of RPL (30). Multiple modification mechanisms of epigenetics may be involved in the pathophysiology of EMs (31).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, DNA methylation-induced gene expression disorders and immunological imbalances affect all phases of embryonic development, which may be linked to RPL pathobiology (29). In addition, clinical studies have found that DNA damage induced by heavy metals may be related to the occurrence and development of RPL (30). Multiple modification mechanisms of epigenetics may be involved in the pathophysiology of EMs (31).…”
Section: Discussionmentioning
confidence: 99%
“…Certain heavy metals such as zinc (Zn), cobalt (Co), copper (Cu) and iron (Fe) are essential at a trace concentration to maintain life by involving in diverse biological functions ( Appenroth, 2010 ; Kim et al, 2019a ). Heavy metals accumulated at high concentrations can pose toxicity in living organisms by destroying membrane and DNA integrities and inhibiting the activity of proteins ( Kim et al, 2015 ; Alrashed et al, 2021 ). For example, chromium (Cr), arsenic (As) and cadmium (Cd) induce DNA repair dysfunction and oxidative stresses, and thereby potentially cause cancers in human ( Balali-Mood et al, 2021 ; Luo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides chromosomal abnormalities, genetic factors, uterine and endocrine abnormalities, chronic exposure to heavy metals have been associated with spontaneous abortions, as well as pre-term deliveries and stillbirths. The metalloestrogen cadmium (Cd) has been linked to retardation of fetal development and spontaneous abortions while lead (Pb) levels over a certain threshold have been associated with implantation failure and early pregnancy loss with strong teratogenic impact (Alrashed et al, 2021;Dutta et al, 2021). Elevated Lead and cadmium levels has been associated with premature rupture of placental membranes, premature delivery and miscarriage (MK., 2019; Taylor, Tilling, Golding, & Emond, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative DNA damage accruing from metal induced OS have been implicated in fetal abnormalities and pregnancy termination (Duhig, Chappell, & Shennan, 2016). Higher levels of such HM as antimony and arsenic have been reported in women with RPL (Alrashed et al, 2021). Reduction in antioxidants and increased lipid peroxidation and oxidative DNA damage have been reported in women with recurrent pregnancy loss (Zejnullahu, Zejnullahu, & Kosumi, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation